"Otherwise, There Would Be No Point in Going to School": Children's Views on Assessment - Simone Seitz; Alessandra Imperio; Petra Auer (MDPI AG, 2023)
Assessment is a much-discussed dimension of school life, as it is deeply connected to teacher-student power relations, where teachers' responsibilities for individual assessment and support coexist. Moreover, children's views are hardly investigated in the research. Studies reflecting those aspects in inclusive school systems, such as the Italian one, are still rare. Assuming assessment is a social practice that shapes classroom differences, in our research project on "Children's Perceptions of Performance in Primary Schools" (CrisP), we conducted 35 narrative interviews with 3rd graders from six schools, framed by classroom observations, to reconstruct their perceptions of performance and assessment and develop individual case portraits through Open Coding as defined within Grounded Theory and the Documentary Method. The study was conducted in the Province of Bolzano (Italy). Children seem aware of the teacher-child power relations that emerge in the assessment field and the reciprocity and interdependence of the two roles. In the reconstruction of Alice's case, she demonstrates she trusts adults but can also work pragmatically on her position, redefining her power role that benefits from teachers' services. Along with a brief overview of crucial findings and the reconstruction of Alice's perceptions, we ask for implications for appropriate assessment practices in inclusive primary schools.